A Study of the Place of the Healing and Deliverance Ministry in Kabarole Archdeaconry, Diocese of Ruwenzori of the Church of Uganda - Kanywa Alfred Muhumuza (Uganda Christian University, 2024)
The study was an investigation of the place of the Healing and Deliverance Ministry in the Church of Uganda setting: with specific reference to Kabarole Archdeaconry, Diocese of Ruwenzori of the Church of Uganda. The specific objectives of the study were: to establish if there are any Healing and Deliverance services in Kabarole Archdeaconry, Diocese of Ruwenzori; find out the reasons why there is no Healing and Deliverance ministry in some churches in Kabarole Archdeaconry, Diocese of Ruwenzori; examine the effects of the lack of the Healing and Deliverance ministry in some Churches in Kabarole Archdeaconry, Diocese of Ruwenzori; and to establish what the Church has done and what more can be done to support the Healing and Deliverance ministry in Kabarole Archdeaconry, Diocese of Ruwenzori. It was found out that healing and deliverance was conducted in some churches with the holistic process of spiritual, emotional and physical wellbeing and wholeness of people. Ignoring the healing and deliverance ministry ignorance about the healing ministry and word of God, lack of theological training, divisionism and confusion about healing and deliverance were some of the reasons for the absence of the healing and deliverance ministry in some churches in Kabarole. The effects of lack of healing and deliverance ministry include: the exodus of Christians from the Church of Uganda to Pentecostal churches and the believers staying in the bondage of Satan due to the lack of healing and deliverance services. The church leaders’ role remains to cultivate an atmosphere of faith and expectation of God's healing and deliverance power to manifest. They are to always encourage the participants to come with faith and anticipation, trusting in God's ability to bring about transformation and wholeness following the participants’ sincere repentance.
Undergraduate Research